Business processes modelling and diagnosis - Santos, J. P.; Ramos, P.; Farinha, J.; Moro, S. (Business Information Review, 2020)
The computerization of relevant information in organizations is increasingly becoming a necessary reality in companies that want to be present in a market that is characterized by innovation, adaptability and where bigger amounts of information are increasingly available and accessible to everyone, the use of Social Collaboration tools in organizations become increasingly crucial to keep a business running (Brocke et al. 2018). In (Alter 2013), work systems are described as systems “in which human participants and machines perform work (processes and activities) using information, technology and other resources to produce specific products/services for specific internal and external customers”. The computerization of processes is not, however, so complete because all the formal and informal relationships among employees, which underlie each organization and have a high impact on the correct definition of processes, are not correctly considered. In order to mitigate this problem, this article presents a proposal for representing, in computer systems, formal and informal relations between employees and the consequent integration in organizational processes in order to provide automatic diagnosis of highlighted processes.